In Vitro Antioxidant Activity of Zingiber officinale, Piper retrofractum, and Their Combinations - Wasito, Hendri; Ekowati, Heny; Hayati, Fitri Fauziah (Indonesian Journal of Cancer Chemoprevention, 2011)
Many  plants  are  used  empirically  as  antioxidant.  Plants  that  are  frequently  used  in Indonesian  communities  are  Zingiber  officinale  and  Piper  retrofractum.  The  aim  of  this  research was  to  investigate  the  in  vitro  antioxidant  activity  of  single  ethanolic  extract  and  the combinations ofZ. officinale and P. retrofratum using free radical scavenging DPPH (1,1-diphenyl-2-picrylhydrazyl)  method.  Z.  officinale  and  P.  retrofratum  were  extracted  by  maceration  using 95%  ethanol  for  3  x  24  hours. Antioxidant  activity  was  evaluated  using  1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The concentration of the extract (μg/mL) that was required to scavenge 50% of free radicals (IC50)was calculatedusing the percent scavenging activities of six different  extract  concentrations.  The  results  showed  that  the  single  ethanolic  extract  of  Z. Officinalle produced the highest antioxidant activity with IC50of 56 μg/mL, while the antioxidant  activity of the single ethanolic extract of  P. retrofractum produced an IC50 of 3.445 μg/mL. The IC50 of combination of Z. officinale and P. retrofratum ethanolic extracts at concentration ratios of 1: 2, 1 : 1, and 2 : 1 were 148 μg/mL, 85 μg/mL, and 73 μg/mL.Key words: Zingiber  officinale, Piper retrfratum, Antioxidant, DPPH